2020
DOI: 10.3390/nano10101901
|View full text |Cite
|
Sign up to set email alerts
|

Surface Wettability of ZnO-Loaded TiO2 Nanotube Array Layers

Abstract: Herein we report on the synthesis and the effects of gradual loading of TiO2 nanotube array layers with ZnO upon surface wettability. Two-step preparation was chosen, where TiO2 nanotube layers, grown in a first instance by anodization of a Ti foil, were gradually loaded with controlled amounts of ZnO using the reactive RF magnetron sputtering. After crystallization annealing, the formerly amorphous TiO2 nanotubes were converted to predominantly anatase crystalline phase, as detected by XRD measurements. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 52 publications
3
11
0
Order By: Relevance
“…The variation in WCAs of the In 2 O 3 : Sn /ZnO thin films since UV treatment is shown in figure 13. Other research has also confirmed that UV illumination leads to a switching behavior from hydrophobic to hydrophilic [61,62]. The potential applications of the results obtained here are numerous, including the production of antifogging mirrors [1], self-cleaning exterior tiles [63], and biomedical fields where surface wettability has an important role in protein adsorption, cell adhesion, and proliferation [64].…”
Section: Wettability Behavior Under Uv Illuminationsupporting
confidence: 71%
See 1 more Smart Citation
“…The variation in WCAs of the In 2 O 3 : Sn /ZnO thin films since UV treatment is shown in figure 13. Other research has also confirmed that UV illumination leads to a switching behavior from hydrophobic to hydrophilic [61,62]. The potential applications of the results obtained here are numerous, including the production of antifogging mirrors [1], self-cleaning exterior tiles [63], and biomedical fields where surface wettability has an important role in protein adsorption, cell adhesion, and proliferation [64].…”
Section: Wettability Behavior Under Uv Illuminationsupporting
confidence: 71%
“…This phenomenon can be attributed to the rod-like ZnO lattice [60]. This evolution follows the Cassie-Baxter model before ultraviolet illumination [61].…”
Section: Wettability Studies Throughout Contact Angle Measurementmentioning
confidence: 65%
“…A typical micro columnar structure of the sensing layer is observed with excellent adhesion [33,34]. From Figure 3d-i, it can be seen that these vertical columnar structures are around 2 μm in height.…”
Section: Characterizationmentioning
confidence: 86%
“…The presence of a mixture of oxide bonds from several elements in the thin films compositions indicates the possibility of obtaining different surface reactivity by customizing their ratio. Modifying the flow of Oxygen and thus its availability during layer growth can influence the stoichiometry of the layers and enhance the presence of suboxides, modifying the energy band configuration in such heterojunction materials [41,42]. This aspect is directly related to the surface reactivity of semiconductor materials (e.g.…”
Section: Technical Applicationsmentioning
confidence: 99%